TISSUE CULTURE STUDY FOR MICROPROPAGATION OF ANY MEDICINAL PLANT - PRIYA (International Journal of Multidisciplinary Research and Studies, 2020)
For a substantial length of time, a large majority of plant species have been used for the production of therapeutic products. Nearly every country and culture make use of the therapeutic capabilities that plants possess as a primary or supplementary source of medical care. Denbath et al. (2006) state that medicinal plants play an important part in many health care systems. [Further citation is required] The estimations supplied by the World Health Organization (WHO) indicate that herbal medicines are capable of satisfying the needs of around 80 percentage of the world's population. This is especially true for the millions of individuals who make their homes in rural areas of emerging nations. Traditional treatments, many of which were derived from plants, formed the basis for the development of a significant portion of today's medications. According to some statistics, one-fourth of all drugs that can be purchased without a prescription either include plant extracts or are based on the chemical structures of plants. The most widely used pain medication, aspirin, was originally derived from several Salix and Spiraea species by chemical synthesis. Additionally, some of the most powerful anticancer medications, such as paclitaxel and vinblastine, are exclusively derived from plant sources. This is the case for both of these medications (Pezzuto, 1996).